Nowe regulacje w polskim prawie podatkowym jako forma pomocy obywatelom Ukrainy – przykład ryczałtu od dochodów spółek (tak zwany estoński CIT) - Antonów, Dobrosława (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article is devoted to the new tax law regulations introduced to help Ukrainian citizens. Due to the large emigration of Ukrainian citizens to Poland, many new solutions have been introduced in the tax law, for instance, tax exemptions for donations for humanitarian aid purposes or reductions in the tax rate. One example of such solutions, discussed in more detail in this article, is the refraining from collecting lump-sum tax on corporate income.
Keywords: Ukraina; obywatel Ukrainy; wojna na Ukrainie; podatek; estoński CIT; zryczałtowany podatek dochodowy od osób prawnych; prawo podatkowe; Ukraïna; gromadâni Ukraïni; vìjna v Ukraïnì; podatok; estonsʹkij SÌT; paušalʹnij platìž vìd pributku pìdpriêmstva; podatkove pravo